2018
DOI: 10.1155/2018/5729198
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment on the Hysteretic Behavior of a Full‐Scale Traditional Chinese Timber Structure Using a Synchronous Loading Technique

Abstract: In traditional Chinese timber structures, few tie beams were used between columns, and the column base was placed directly on a stone base. In order to study the hysteretic behavior of such structures, a full-scale model was established. e model size was determined according to the requirements of an eighth grade material system specified in the architectural treatise Ying-zao-fa-shi written during the Song Dynasty. In light of the vertical lift and drop of the test model during horizontal reciprocating motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Dutu et al (2016), Vieux-Champagne et al (2014), and Xie et al (2019) investigated the seismic performance of timber frame systems with infill by cyclic load tests. Wu et al (2018), Fang et al (2001), and Shi et al (2018) conducted experimental and numerical simulation studies on traditional Chinese timber frame structures to investigate their stiffness, damage modes, and other properties. Ali et al (2012;, Yeo et al (2016), and Kaori (2019) investigated the dynamic performance of timber frame structures through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Dutu et al (2016), Vieux-Champagne et al (2014), and Xie et al (2019) investigated the seismic performance of timber frame systems with infill by cyclic load tests. Wu et al (2018), Fang et al (2001), and Shi et al (2018) conducted experimental and numerical simulation studies on traditional Chinese timber frame structures to investigate their stiffness, damage modes, and other properties. Ali et al (2012;, Yeo et al (2016), and Kaori (2019) investigated the dynamic performance of timber frame structures through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Xue et al [3,4] carried out some pseudo-static tests and shaking table tests on timber structures with mortise-tenon joints and found that most of the input energy is dissipated by the mortise-tenon joints. Shi et al [5] used a synchronous loading technique to study the hysteresis behavior of a full-scale Chinese timber structure and revealed the effects of vertical loads and gaps in the mortise-tenon joint. Some tests on the timber frame with straight mortise-tenon joints [6,7] or with dovetail joints [8][9][10][11] have been conducted and the pulling-out of the tenon were frequently observed.…”
Section: Introductionmentioning
confidence: 99%